2022
DOI: 10.1111/pim.12943
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variant‐based genome wide association study reveals immune‐related genes associated with parasite resistance in a heritage sheep breed from the United States

Abstract: Florida Native is a heritage sheep breed in the United States and expresses superior ability to regulate gastrointestinal nematodes. The objective of the present study was to investigate the importance of copy number variants (CNVs) on resistance to natural Haemonchus contortus infections. A total of 300 Florida Native sheep were evaluated. Phenotypic records included fecal egg count (FEC, eggs/gram), FAMACHA© score, percentage cell volume (PCV, %), body condition score (BCS) and average daily gain (ADG, kg). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…Other differentially expressed genes and transcripts detected here were previously associated with the response to H. contortus, such as GAST [72] and FGF14 [73] in sheep and RORC in goats [74], and to Trichostrongylus colubriformis, such as GNLY [75]. Some of the genes were associated with weight, body conformation, and growth traits, such as LRRC8B [76] and IGF1 [77]; adaptation, such as ABCC11 for desert adaptability [78], GNGT1 for hypoxia [79] [90], response against O. ostertagi vaccination in cattle, such as DHRS9 [91], and lipoxygenases (ALOXE3, ALOX12, ALOX12B, and ALOX15 genes) associated with the in ammatory response in mice [92].…”
Section: Discussionsupporting
confidence: 55%
“…Other differentially expressed genes and transcripts detected here were previously associated with the response to H. contortus, such as GAST [72] and FGF14 [73] in sheep and RORC in goats [74], and to Trichostrongylus colubriformis, such as GNLY [75]. Some of the genes were associated with weight, body conformation, and growth traits, such as LRRC8B [76] and IGF1 [77]; adaptation, such as ABCC11 for desert adaptability [78], GNGT1 for hypoxia [79] [90], response against O. ostertagi vaccination in cattle, such as DHRS9 [91], and lipoxygenases (ALOXE3, ALOX12, ALOX12B, and ALOX15 genes) associated with the in ammatory response in mice [92].…”
Section: Discussionsupporting
confidence: 55%
“…Riggio et al [61] discovered that QTL 193038 was associated with strongyle FEC at 24 weeks old. Estrada-Reyes et al [47] also identified the same QTL associated with H. contortus FEC and PCV measured on drench day and 38 days later. The second QTL (13989) was initially identified by Gutiérrez-Gil et al [58] as associated with FEC on day 60.…”
Section: Chromosome 10mentioning
confidence: 79%
“…The growth arrest specific 6 (GAS6) gene was suggested as a wide controller of the innate immune system [119]. Estrada-Reyes et al [47] investigated the copy number variant (CNV) associated with H. contortus FEC, PCV, FAMACHA©, BCS, and average daily gain in Florida Native sheep at two different sampling time points. First, on drench day, when animals around three to five months old were drenched and released for grazing and natural infection, and at a second timepoint at 38 days after drenching.…”
Section: Chromosome 10mentioning
confidence: 99%
“…This discovery offers a potential explanation for the remarkable resistance of these goat breeds against infectious diseases. In the case of Florida Native sheep, Estrada-Reyes et al ( 41 ) delved into the genetic underpinnings of resistance against gastrointestinal nematodes. Their meticulous investigation revealed that 14 CNVs exhibited overlaps with QTLs associated with gastrointestinal nematode resistance.…”
Section: Cnvs and Their Association With Phenotypic Traits In Herbivo...mentioning
confidence: 99%
“…Notably, recent research endeavors have delved into the investigation of the association between CNV in specific genes and a variety of phenotypic traits in animals, including growth characteristics in cattle ( 27 , 28 ), goats ( 29 31 ), sheep ( 32 ) and horses ( 33 38 ). These studies have also extended their focus to examine the link between CNVs and other vital phenotypes, such as reproduction traits ( 39 , 40 ) and disease resistance ( 7 , 41 ). These studies have unveiled CNV as a key player linked to diverse facets of phenotypic diversity and economic traits in animal realms.…”
Section: Introductionmentioning
confidence: 99%